PRISM BRAIN MAPPING – NEUROSCIENCE APPLICATION IN BUSINESS COACHING - Czerwiec, Marta; Wujec, Bozena (Psychological Prospects Journal, 2018)
The article addresses coaching as the emerging field of human development from the neuroscience perspective. Neuroscience explains human behavior in terms of activities of the brain, and therefore can make a major contribution to the effectiveness of the coaching process, as well as of the coaching relationship. Introducing neuroscientific models, methods and tools into the research in the field of coaching can raise the awareness of existing behavioral patterns of coaches as well as enhance understanding of the mechanism, which enable coaches to adapt their behaviors accordingly.In this paper we present the results of our preliminary study on the aptitudes and characteristics, which – from the neuroscience point of view, make coaches successful. As we have based our research on the neuroscience insights, we have chosen the neuroscience-based tool, PRISM Brain Mapping questionnaire, to measure aptitudes and preferred behaviors of successful coaches. From the perspective of our research, the most important issue was to investigate the most preferred behavioral patterns among successful coaches, versus the less experienced coaches, or beginners.Findings from our research can be useful in supporting professional development of coaches, by enabling them to assess their possible competence gap and to address it on the individual level. Now, it is scientifically proved that our brains have got plasticity, and therefore, one can change the behavioral patterns to better suit in the role of a good coach.